2022
DOI: 10.4178/epih.e2022110
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality in Korea during the first year of the COVID-19 pandemic

Abstract: Objectives: This study aimed to examine the trends in total mortality between 1998 and 2020 and to compare the changes in a wide range of detailed causes of death between 2020 during the COVID-19 pandemic and the previous year in Korea. Methods:We used registered population and mortality data for the years 1998-2020 obtained from Statistics Korea. The age-standardized all-cause mortality rate and the annual percent change between 1998 and 2020 were determined. The rate ratio and rate difference of the age-stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Mortality due to accidents had an excess of nearly 4%, which was not statistically significant. Consistent with the findings of the present study, The mortality due to accidents increased insignificantly in Norway and Minnesota and decreased by nearly 2% in South Korea ( 1 , 12 , 20 ). Even before and during COVID-19, accidents were the most important cause of death in the 5–44 age group, which shows that COVID-19 has not been able to cause a significant impact on this age group and to reduce the death of young people, the number of accidents should still be reduced.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Mortality due to accidents had an excess of nearly 4%, which was not statistically significant. Consistent with the findings of the present study, The mortality due to accidents increased insignificantly in Norway and Minnesota and decreased by nearly 2% in South Korea ( 1 , 12 , 20 ). Even before and during COVID-19, accidents were the most important cause of death in the 5–44 age group, which shows that COVID-19 has not been able to cause a significant impact on this age group and to reduce the death of young people, the number of accidents should still be reduced.…”
Section: Discussionsupporting
confidence: 92%
“…Excess deaths due to Neoplasms were reported in Latvia within 3 weeks of their study and had a significant positive excess of death, but the total excess mortality from malignant neoplasms was not significant ( 4 ). On the other hand, mortality due to Neoplasms has significantly decreased during the COVID-19 pandemic in South Korea (3%), São Paulo (1.5%), and Minnesota (2%), and did not significantly change in Norway ( 1 , 11 , 12 , 20 ). Excess deaths due to Neoplasms in South Khorasan during the COVID-19 pandemic are partly due to the population aging and the health transition ( 23 ) as well as the reduced screening and delayed cancer treatments due to limited health care sources available for cancer treatment during the COVID-19 ( 26 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Between 2009 and 2021, suicide was the leading cause of death among adolescents in Japan [59,60]. Although suicide rates among adolescents have globally been increasing over time, most studies from other OECD countries have reported that adolescent SMRs decreased or remained unchanged during the pandemic [61][62][63][64][65], whereas in Japan, it has been reported that the SMRs of both males and females under 20 years old increased during the pandemic [39][40][41]66,67]. These reports attributed the increase in adolescent SMRs to major lifestyle changes during the pandemic, particularly pertaining to the impaired ability to engage in recreational and educational opportunities and being forced to spend much of their time at home due to social restriction measures [39][40][41]66,67].…”
Section: Suicides Among Adolescents and The Elderlymentioning
confidence: 99%